All fiber mode-locked thulium-doped fiber laser using a novel femtosecond-laser-inscribed 45°-plane-by-plane-tilted fiber grating - Kanagaraj, Nithyanandan; Theodosiou, Antreas; Aubrecht, Jan; Peterka, Pavel; Kamradek, Michal; Kalli, Kyriacos; Kašík, Ivan; Honzátko, Pavel (My University, 2019)
Using the novel 45°-plane-by-plane-tilted fiber grating inscribed by a femtosecond laser as an in-line fiber polarizer, we demonstrate an all-fiber passively mode-locked thulium-doped fiber laser. We characterize the grating for polarization-dependent loss, indicating high contrast and broad operating wavelength. The 45°-tilted fiber grating together with polarization controller act as an artificial saturable absorber suitable for mode-locking through nonlinear polarization rotation. By properly pre-adjusting the polarization controller, stable mode-locking is achieved for a pump power in the range of 300 mW-400 mW at 1565 nm. Owing to the net anomalous dispersion, a stable mode-locked soliton pulse centered at 1870 nm with a pulse width of 862 fs is reported at a fundamental repetition rate of 22.34 MHz. A long-term stability test reveals that the laser is quite stable for 24 h under laboratory conditions, confirming the capabilities of the 45°-tilted fiber grating for stable laser operation.
Keywords: Dissipative soliton; Fibre lasers; Soliton mode-locking; Thulium doped fibre; Tilted fiber Bragg grating